Dietary Sanguinarine Mitigates Clostridium perfringens-Induced Enteric Challenge in Broiler Chickens: Effects on Productive Performance, Metabolic Status, Antioxidant Capacity, Immune Response, and Intestinal Health - Ali R. Al Sulaiman; Ala E. Abudabos (Life, 2026)
This study evaluated the efficacy of graded dietary sanguinarine as a phytobiotic alternative for mitigating Clostridium perfringens-induced enteric challenge in broiler chickens. A total of 360 newly hatched Ross 308 broiler chicks were randomly assigned to six treatments: a non-challenged negative control, a challenged positive control, a challenged group supplemented with avilamycin at 0.10 g/kg, and three challenged groups supplemented with sanguinarine at 0.06, 0.09, or 0.12 g/kg diet. Birds were reared for 35 days, and all challenged groups received repeated oral inoculations with Clostridium perfringens following an initial Eimeria spp. challenge. Compared with the positive control, all sanguinarine doses improved cumulative average daily gain, feed conversion ratio, and European production efficiency factor to levels comparable with the negative control and avilamycin groups. Sanguinarine at 0.09 and 0.12 g/kg restored dressing percentage, whereas all doses improved breast yield and increased relative bursa weight beyond both control and avilamycin values. All sanguinarine treatments normalized serum total protein, glucose, total antioxidant capacity, and superoxide dismutase activity, with stronger recovery of superoxide dismutase than avilamycin. In the ileum, all sanguinarine doses increased villus length above the avilamycin and negative control groups, while maintaining comparable villus width. Sanguinarine also improved immune status by restoring serum immunoglobulin Y, interleukin-2, and interferon-gamma concentrations, reducing interleukin-1 and interleukin-6 more effectively than avilamycin, and fully restoring immunoglobulin A at the highest dose. Moreover, sanguinarine reduced harmful bacterial populations and promoted beneficial ileal bacteria across the tested inclusion levels. Overall, dietary sanguinarine, especially at 0.09–0.12 g/kg, may serve as a promising non-antibiotic nutritional strategy for improving broiler resilience under enteric challenge conditions.